An Evaluation of the Contribution of African Traditional Medicine to Healthcare Delivery: A Case Study of Selected Herbal Centres in Akuapem, Ghana - Henry Kwaku Adu-Offei; John Kwaku Opoku (E-Journal of Humanities, Arts and Social Sciences)
Traditional medicine has become indispensable in contemporary healthcare delivery in both rural and urban communities in Ghana and beyond as it is patronized by people of various social statuses. The purpose of this study is to comprehend the weaknesses and strengths of traditional medicine preparation, administration, and use within Ghana’s healthcare system. With the use of a semi-structured interview guide, purposive and random sampling techniques were employed in this qualitative study to gather data from a well-established traditional medical facility as well as two native healers all in the Akuapem enclave of Ghana. It was noted that despite significant setbacks such as poor preservation and storage of herbs and medications, a lack of labeling and expiration dates, and noncompliance with quality control and assurance procedures among others in the operations of certain local herbalists, traditional medicine has been improved in some areas through the application of contemporary scientific and technological knowledge. To enhance their practices and optimize the benefits of traditional medicine, the study suggests assistance for the many herbal medicine practitioners who are operating clandestinely and outside of the accepted standards. The study provides empirical evidence on the evolution of African traditional medicine and identifies areas for improvement to enhance its significance in Ghana’s healthcare delivery. It also emphasizes the necessity for effective collaboration between conventional healthcare providers and traditional health practitioners in the delivery of quality healthcare in Ghana.